Political and Economic Justifications for Conditional Trade Barriers: Anti-Dumping Duty, Safeguard Measure and National Security Exception - Abdul Razak Nasution (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Long-term economic and trade cooperation. For the next stage, OKI is expected to lead to higher economic development, such as cooperation in the financial sector. This paper will discussed the possibility of OIC member countries work together to form a common currency area. They use the VAR method approach to test the possibility of a common currency area among OIC member countries. Starting with countries in the Middle East region such as Iran, Iraq, Kuwait, Qatar, Saudi Arabia, and the United Arab Emirates, data analysis from 1975-2011 shows that it is possible to establish a common currency area before finally being used as a reference for the formation of the region. Common currency within the scope of OIC members. The study results show that demand and supply fluctuations align with structural fluctuations in five countries (Iran, Iraq, Qatar, Saudi Arabia, and the United Arab Emirates). This indicates a standard exchange rate system pegged to a particular currency, namely the US Dollar. There is an opportunity for economic integration at a higher level. However, for Kuwait, which is opposite to the other five countries, it can be caused by various factors such as differences in the monetary system to patterns of economic growth and macro policies in the local country. So that these factors can also be an inhibiting factor for the occurrence of a common currency area between companies OIC members.